Performance and Production Cost of Klanting Agroindustry in Gantimulyo Village Pekalongan Subdistrict East Lampung - Putu Shabna Dewi; Ktut Murniati; Maya Riantini (Politeknik Negeri Lampung, 2021)
The purpose of this study was to analyze the raw material procurement process with the six right concept (time, place, type, price, quality, and quantity), production performance and production costs of the Klanting agro-industry in Gantimulyo Village, Pekalongan District, East Lampung Regency. The research method used is the case study method. This research was conducted in three Klanting agro-industries in Pekalongan District. The research location was chosen purposively with the consideration that Gantimulyo Village is the center of Klanting production in East Lampung Regency. The respondents of this research are the owners and consumers of the agro-industry. Data collection was conducted from January to February 2020. The analytical method used is descriptive qualitative and quantitative analysis methods. The results showed that the procurement of raw materials in the Klanting agro-industry was not appropriate. Klanting agro-industrial production performance in Gantimulyo Village has not been said to be good because two of the five production performance indicators, namely the indicators of capacity and flexibility, have not been optimally implemented by the three klanting industries. Klanting production costs in the Klanting agro-industry are below the selling price. This means that the klanting agro-industry in Gantimulyo Village is profitable and feasible to run